The attention network characteristics of adults with high ADHD traits: low stability, boost accuracy by sacrificing response time - Xiang, Jie; Wang, Xueke; Feng, Tingyong (Frontiers in Psychology, 2024)
Adults with high ADHD traits (H-ADHD) face challenges in academics, social interactions, and careers, yet their attention characteristics remains unclear. Using Attention Network Test (ANT), we examine attentional characteristics (including specific attentional qualities and overall attentional performance) of H-ADHD and explore how their specific attentional qualities impact overall attentional performance. We find H-ADHD primarily manifests lower alerting network, higher intra-individual coefficient of variation (ICV) and poorer balanced integration score (BIS). These results remain stable even after controlling for covariates such as anxiety and depression scores. Furthermore, the BIS deficiency in high attention deficit traits group (H-ADHD-I) specifically manifests as “high accuracy—slow reaction time,” reflecting their response pattern as the reaction time compensated accuracy. Additionally, compared to alerting network, attentional variability (ICV) has a greater role in mediating the impact of ADHD symptoms on overall attentional performance (BIS). Taken together, H-ADHD mainly exhibit deficits in sustained attention (alerting network), attentional stability (ICV), and overall attentional performance. ADHD symptoms worsen overall attentional performance due to increased attentional variability. The study emphasizes the sensitivity of alerting network, ICV, and BIS indicators, and highlights the significance of attentional variability, suggesting their potential clinical value in the future.